Stressful life events in childhood and adulthood and risk of physical, psychological and cognitive multimorbidities: a multicohort studyResearch in context - Yaguan Zhou; Mika Kivimäki; Julianne Holt-Lunstad; Lijing L. Yan; Yue Zhang; Hui Wang; Sunyi Wang; Xiaolin Xu (EClinicalMedicine)
Summary: Background: Stressful life events, such as financial hardship, and death of own child, have been associated with various adverse health outcomes, but their impacts on complex multimorbidities remain unknown. This study examined the association between stressful life events in childhood and adulthood and later-life physical, psychological and cognitive multimorbidities. Methods: We harmonised and pooled longitudinal data from three nationally representative cohort studies from the Program on Global Ageing, Health and Policy: the US Health and Retirement Study (HRS), the English Longitudinal Study on Ageing (ELSA), and the China Health and Retirement Longitudinal Study (CHARLS), encompassing the years 2011–2020. Participants were middle-aged and older adults free from physical, psychological and cognitive multimorbidities and with information on six stressful life events in childhood and six stressful life events in adulthood. Multimorbidities were measured according to the coexistence of physical, psychological and cognitive conditions. Three lifestyle factors, including physical inactivity, alcohol consumption, and smoking, were treated as potential mediators. We used Cox proportional hazards regression models and multi-state models to estimate the risk of developing or progressing multimorbidities at follow-up in the pooled population and in each study. Findings: In the 24,955 participants (mean age 63.6 years, standard deviation 10.6), 4284 (17.2%) reported stressful life events in childhood, 6509 (26.1%) in adulthood, and 5364 (21.5%) in both. During a follow-up of 8–9 years, 10,913 (43.7%) participants developed physical, psychological and cognitive multimorbidities. After adjusting for age, sex, study, and education, individuals with both childhood and adulthood stressful life events experienced a 1.71 (vs. none, hazard ratio: 1.71, 95% confidence interval: 1.54–1.90), 1.26 (1.16–1.38), 1.58 (1.22–2.04), and 1.89 (1.69–2.11) times higher risk of physical–psychological multimorbidity, physical–cognitive multimorbidity, psychological–cognitive multimorbidity, and physical–psychological–cognitive multimorbidity respectively. The associations with multimorbidities that included a psychological condition as one component were stronger than those that included only physical or cognitive conditions. Childhood stressful life events were associated with transitions from baseline to physical–psychological and psychological–cognitive multimorbidities, while adulthood and life-course stressful events were associated with all transitions between baseline and multimorbidities (≥2 adulthood events vs. 0 and transition to physical, psychological and cognitive multimorbidity: 1.73, 1.43–2.09). Smoking status, physical inactivity, and alcohol consumption partially mediated the associations, and the strongest mediation effect was observed for alcohol consumption which accounted for 18.2% of the associations between childhood stressful life events and physical–cognitive multimorbidity. Interpretation: From the studied cohorts middle-aged and older adults with a history of stressful life events in childhood or adulthood were seen to be at increased risk of developing multimorbidities involving psychological, physical and cognitive conditions. These findings emphasise the importance of preventive strategies targeting both social and lifestyle factors throughout the life course. Funding: Natural Science Foundation of China, Hundred Talents Program Research Initiation Fund from Zhejiang University, Fundamental Research Funds for the Central Universities.